The Relationship Between Leadership and Management and Quality Management: Systematic Literature Review - Tóth, Barna; Szűcs, Edit (International Journal of Engineering and Management Sciences, 2025)
This publication is intended to examine the close relationship between quality management and leadership and organization, highlighting the possibilities of increasing organizational efficiency in both industrial and non-industrial environments. During the systematic literature review, we examined the role of leadership, the closely related organizational culture, and quality management. The publication aims to explain how quality systems and frameworks, such as ISO and the EFQM model, support strategic planning and sustainability, thus providing direction for modern organizations. The research emphasizes the importance of digital transformation and knowledge management, and we have formulated the future research goals that can advance the productivity of organizations.